Influence of Professional Career Development and Teamwork on Employee Job Satisfaction: Evidence From Private Universities in Nigeria - Adani Nnenne Ifechi; Ifeanyi E. Nuel Okoli; Kanayo Chike Nwosu (Journal La Bisecoman, 2022)
The purpose of this study was to examine the influence of professional career development and teamwork on job satisfaction among lecturers in selected private universities in Nigeria. Social exchange theory was used to establish the theoretical framework of this study. The study adopted descriptive survey research design to establish the relationship between professional career development, teamwork and job satisfaction. Structured questionnaire was distributed to 428 respondents in six selected private universities in Nigeria. The reliability of the measuring instrument was tested using Cronbach Alpha. Hypothesis one was tested using correlation analysis and regression analysis were employed for testing of hypotheses two, three and four. The result of the analysis showed that there is a statistical influence between the three constructs professional career development, teamwork and job satisfaction of private university lecturers in Nigeria. The research concludes that professional career development and teamwork exert different levels of influence on private university lecturers’ job satisfaction and that teamwork exerts greater level of influence on lecturers’ job satisfaction. Hence it was suggested that management of private universities should promote the establishment of multidisciplinary and interdisciplinary research teams and centres in order to blend the experience of academics. Also, private universities should make annual plans to sponsor or subsidize conferences, seminars and workshop expenses of lecturers in order to encourage frequent participation in academic events so as to sustain the lecturer’s satisfaction and commitment on the job.